(untitled) (Journal of Hama University, 2024)
The search aimed to know the level of psychological stress among patients with arterial hypertension in the city of Lattakia, and the researcher used the descriptive approach The study sample consisted of (50) patients with arterial hypertension who were randomly selected (21) males and (29) females. The researcher chose the stress scale for patients with arterial hypertension, modified from the psychological stress scale for diabetics, prepared by Jassim Muhammad Al-Marzouki. The scale consisted of (71) statements over five dimensions: social stress, cognitive stress, emotional stress, economic stress, and physical stress. The search results showed the following: 1 The level of psychological stress among patients with arterial hypertension was of a weak degree. 2- There are statistically significant differences in the level of psychological stress among patients with high blood pressure, according to the gender variable in favor of females. 3- There are no statistically significant differences in the level of psychological stress according to the variable of social status.